Analysis of the Impact of Foreign Direct Investment in Renewable Energy on Pollution Emissions in Low-, Middle-, and High-Income Countries in the Middle East - Khoz, Ashkan; Baghfalaki, Afshin; Peykarjou, Kambiz; Memarnejad, Abbas (Business, Marketing, and Finance Open, 2025)
Environmental issues have been a significant economic concern in both developing and developed economies in contemporary times, highlighting the fact that human activities have inflicted irreversible damage on the planet. Therefore, this study aims to examine this critical issue. The objective of this research is to investigate the effect of factors such as gross domestic product (GDP), healthcare expenditures, foreign direct investment (FDI), energy consumption, and population density on carbon dioxide (CO₂) emissions in Middle Eastern countries over the period 2013–2023. To achieve this, the two-step generalized method of moments (GMM) was employed using EViews 10 software. The research findings indicate that foreign direct investment and energy consumption have a negative and significant effect on pollution emissions, whereas healthcare expenditures have a positive impact.